Nutritional management in geriatric traumatology - Singler, Katrin; Goisser, Sabine; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2016)
The prevalence of malnutrition or the risk of malnourishment is high among orthogeriatric patients and a poor nutritional status is associated with a negative outcome. A comprehensive management of preoperative and postoperative nutritional and fluid intake in these patients can help to improve the situation. The management includes identification of patients affected, a thorough assessment of the nutritional status, work-up of possible underlying causes, documentation of nutritional and fluid intake and, most importantly, procedures to improve the preoperative and postoperative nutritional situation. This article gives an overview of the recently updated recommendations on nutritional management in orthogeriatric patients as published by the orthogeriatric working group of the German Geriatric Society.
Keywords: Malnutrition; Weight loss; Mini nutritional assessment; Fluid intake; Nutritional supplements